Impact of Information Booklet on Harmful Effect of Use of Plastics in Relation to Knowledge among Urban Resident of Pune - Hesham Abdulrab Homaid1 , Rushikesh Savant1 , Anjali Chauhan1 , Sonopant.G Joshi2, Ranjana Chavan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Plastics are a wide variety of combinations of properties when viewed as a whole. They areused for variety of items and the list could go on and on and it is obvious that much of what we have todaywould not be possible without plastics. Material and Methods: An experimental study was conducted onknowledge of community regarding harmful effects of plastics among urban residents of Pune city. The preexperimental design was adopted and 40 samples were selected through simple random sampling technique.The data was obtained from the participants using an interview method which included details on sociodemographics of the participants, knowledge of plastics. The same Questionnaire were administered afterproviding informational booklet as well. Result: The findings revealed that pre-test score of the knowledgeof participants was 53.92 % whereas 87.83 % of post test score, to test the effectiveness paired ‘t’ was appliedat the significance level 0.05 and result shows the booklet on harmful effects of plastics was effective.